Evidence for thermal spike effects in ion-irradiated Ni3Al - Jenkins, M; Mavani, P; Muller, S; Abromeit, C (1999)
The influence of the irradiation temperature Ti, on the development of disordered zones produced at displacement cascades in Ni3Al by heavy-ion irradiation with 50 keV Ta+ and 300 keV Ni+ ions has been investigated. The normalised number density (yield) of disordered zones for 300 keV Ni+ irradiation showed a sharp fall between T-irr = 373 K and 573 K. For 50 keV Ni+ irradiation there was a similar fall between 573 K and 673 K. The mean diameters of the disordered zones produced by 300 keV Ni+ ions decreased by about 2 nm between room temperature and 573 K, and there was a tendency for larger zones to become more regular in shape. For 50 keV Ta+ ions, a similar trend was observed between 573 K and 873 K. An annealing experiment confirmed that disordered zones produced at lower temperatures were stable up to a temperature of about 673 K, showing that these trends cannot be due to thermal annealing of disordered zones. The experimental results are consistent with an increased tendency for reordering at the peripheries of disordered zones, due to the increased lifetimes of thermal spikes at higher irradiation temperatures.